Understanding and Attitude of Nursing Study Program Students in Supporting Local Government Programs to Alleviate Stunting Emergencies in South Aceh - Fathimi Fathimi; Dewi Marianthi; Yenni Sasmita; Desriati Devi; Hasniah Hasniah (Green Publisher Indonesia, 2025)
Stunting is still a significant public health problem in South Aceh, potentially threatening the healthy and intelligent generation. The Health Office and DP3AKB of South Aceh Regency carried out stunting cracks to deal with this issue, which is part of the national development agenda. Stunting not only inhibits children's physical growth, but also interferes with brain development, affecting their mental and academic abilities. In 2021, the prevalence of stunting among children under five in South Aceh reached 27.3%, better than other regions in Aceh, but still far from the national target of 14% in 2024. This study aims to determine the relationship between understanding and attitudes of nursing students in supporting local government programs to overcome stunting. The method used is observational with a cross-sectional study design. The results showed that 73% of students had a good understanding of stunting, and 68% showed a positive attitude towards government programs. The final analysis emphasizes the importance of increasing public understanding of stunting, with the active role of final year students expected to strengthen support for local government programs in an effort to alleviate the stunting problem in South Aceh.